Genre Expectations and Viewer Reaction to Our Planet: Are Audiences Motivated to Act More Sustainably? - Ahn, Claire (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2021)
As more people turn to documentaries to learn about environmental issues it becomes even more important to consider the ways in which genre and its representational patterns, such as the use of images, affect viewers. Re-examining the multiliteracies framework and grounded in rhetorical genre studies, this paper explores the first two episodes of Our Planet, a Netflix docu-series that catalyzed strong responses based on two jarring image sequences. The purpose of this paper is to examine how our familiar understandings of particular genres impacts our understanding of particular issues and what happens when the familiar patterns of a genre are challenged.